The CORONA Model in Improving Students' Scientific Writing Skills: Is it Effective? - Muhsyanur (Jurnal Pendidikan Indonesia, 2022)
Scientific writing is one of the language skills that needs to be developed for students. But in reality, there are still many students who have problems with writing. Based on this phenomenon, it is necessary to present a model in scientific writing. One of the models presented in this study is the CORONA model. This study aims to analyze the validity and effectiveness of the CORONA model. This research was conducted through Focus Group Discussion (FGD) from language education experts. This study applies a weak experiment, which is a pre-experimental design with one group pre-test and post-test design. The research sample consisted of two groups, each of which consisted of 26 students. Prior to learning with the CORONA model, students were given a pre-test on scientific writing skills, as well as after learning was carried out students were given the same test. Data was collected using instrument validity sheets and tests. Data on the validity and reliability of the model were analyzed by expert agreement, while data on students' scientific writing skills were analyzed by pair t-test, n-gain, and two means similarity test. The results showed that: content and construct validity were valid each category with a score of 3.3 and 3.5; and reliable with a score of 85.90% and 85.53%. In addition, the results of the study also showed that there was a significant increase in students' scientific writing skills with the mean n-gain being in the high category and not different for the two groups.